Islamic Micro Finance and Its Impact on Poverty Reduction of Two Village Models in Bogor, Indonesia - Mustica Bintang Sabiti; Jaenal Effendi (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2017)
The purpose of this paper is to identify the effectiveness of Islamic microfinance institutions and their impact on poverty reduction in two types of rural areas in the district of Bogor, Indonesia. This research uses descriptive analysis, using a likert’s scale and with a paired sample t test to determine the impact of Islamic micro finance to micro business performance. Multiple regression is also used to see the effect of the types of villages in the implementation of micro-enterprise businesses. The results show that the Islamic micro financing has affected the effectiveness of the income and expenditure aspects, but also quite effective in the aspect of profit and use in expenditure. Furthermore, funding-based Islamic microfinance also has a positive influence on business micro and poverty reduction.DOI: 10.15408/sjie.v6i1.4337